Narrative Theory in Clinical Social Work Practice - McTighe, John P. (Essential Clinical Social Work Series,, 2018)
This theory-to-practice guide offers mental health practitioners a powerful narrative-based approach to working with clients in clinical practice. It opens with a primer on contemporary narrative theory and offers a robust framework based on the art and techniques of listening for deeper, more meaningful understanding and intervention. Chapters expand on these foundational concepts by applying them to a diverse range of populations and issues, among them race and ethnicity, human sexuality, immigration, and the experience of trauma, grief, and loss. The author's engaging voice, thoughtful pedagogical style, and extensive use of examples and exercises also work together to inform the reader's own narrative of growth and self-knowledge. Included in the coverage: • Encountering the self, encountering the other: narratives of race and ethnicity. • Surviving together: individual and communal narratives in the wake of tragedy. • Spiritual stories: exploring ultimate meaning in social work practice. • Sexual stories: narratives of sexual identity, gender, and sexual development. • Leaving home, finding home: narrative practice with immigrant populations. • Moving on: narrative perspectives on grief and loss. Narrative Theory in Clinical Social Work Practice is geared toward students as well as seasoned social workers, and professionals and practitioners in related clinical fields interested in informing their work with a narrative approach.